2018
DOI: 10.3389/fncel.2018.00306
|View full text |Cite
|
Sign up to set email alerts
|

Switching of the Microglial Activation Phenotype Is a Possible Treatment for Depression Disorder

Abstract: Major depressive disorder (MDD) is a common emotional cognitive disorder that seriously affects people’s physical and mental health and their quality of life. Due to its clinical and etiological heterogeneity, the molecular mechanisms underpinning MDD are complex and they are not fully understood. In addition, the effects of traditional drug therapy are not ideal. However, postmortem and animal studies have shown that overactivated microglia can inhibit neurogenesis in the hippocampus and induce depressive-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
158
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(179 citation statements)
references
References 128 publications
3
158
0
1
Order By: Relevance
“…In the present study, we found that CSDS resulted in depressivelike behaviors including increased immobility duration in FST, decreased social interaction ratio in SIT, and decreased time spent in the light area in LDT, accompanied by increased TLR4 protein level in hippocampus. Hippocampus is considered to be one of the most (Kubera, Obuchowicz, Goehler, Brzeszcz, & Maes, 2011;Tang et al, 2016;Zhang, Zhang, & You, 2018;Zhao et al, 2019). In this study, by using the antidepressant fluoxetine, TLR4 inhibitor, and TLR4 knockout Con, control; KO, knockout; SD, stress; TNF-α, tumor necrosis factor-α; TLR4, Toll-like receptor 4; WT, wild-type mice, our results suggest that hippocampal TLR4 is involved in behavioral despair induced by CSDS.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the present study, we found that CSDS resulted in depressivelike behaviors including increased immobility duration in FST, decreased social interaction ratio in SIT, and decreased time spent in the light area in LDT, accompanied by increased TLR4 protein level in hippocampus. Hippocampus is considered to be one of the most (Kubera, Obuchowicz, Goehler, Brzeszcz, & Maes, 2011;Tang et al, 2016;Zhang, Zhang, & You, 2018;Zhao et al, 2019). In this study, by using the antidepressant fluoxetine, TLR4 inhibitor, and TLR4 knockout Con, control; KO, knockout; SD, stress; TNF-α, tumor necrosis factor-α; TLR4, Toll-like receptor 4; WT, wild-type mice, our results suggest that hippocampal TLR4 is involved in behavioral despair induced by CSDS.…”
Section: Discussionmentioning
confidence: 72%
“…Hippocampus is considered to be one of the most important areas involved in stress and depression. For example, neuroinflammation, apoptosis, reduced neurogenesis, and dysfunction of microglia in hippocampus are associated with depression (Kubera, Obuchowicz, Goehler, Brzeszcz, & Maes, ; Tang et al, ; Zhang, Zhang, & You, ; Zhao et al, ). In this study, by using the antidepressant fluoxetine, TLR4 inhibitor, and TLR4 knockout mice, our results suggest that hippocampal TLR4 is involved in behavioral despair induced by CSDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result supports our previous hypothesis that the antidepressant effect of ASA Ⅵ is potentially mediated by inhibiting LPS-induced activation of microglia and neuroinflammation. Microglia activation plays an important role in the development of depression (Zhang et al 2018). Neuroinflammatory injury is considered to be one of the main reasons that microglia cells aggravate the pathological process of depression (Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Mitochondria have been considered to play key roles in these changes in depression. [19][20][21] Mitochondria have been considered to play key roles in these changes in depression.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%